Dental Health Education for Pregnant Women to Prevent Stunting - Sekar Restuning; Irwan Supriyanto; Devy Octaviana; Bayu Irianti (Poltekkes Kemenkes Kupang, 2024)
Poor oral and dental health in pregnant women can affect the fetus, leading to preterm birth and low birth weight. Oral cavity infections can transmit infections to the fetus through the bloodstream. Pregnant women with insufficient knowledge about stunting are at higher risk of contributing to stunting. Dental and oral health promotion is a process of providing information based on the needs of oral and dental health, aiming to achieve good oral and dental health. This study aims to determine the effect of educational videos on the knowledge level of pregnant women in preventing stunting. The research design used in this study is Quasi-Experimental, with a quantitative approach involving pre-tests and post-tests. The analysis results using the Wilcoxon test showed a p-value = 0.000 (p < 0.05), indicating a significant effect on knowledge before and after the intervention using oral and dental health educational videos for pregnant women in preventing stunting. Video media has advantages such as providing closer observation of movements, saving time, and allowing repeated playback, facilitating the knowledge absorption process. Videos are categorized as audiovisual media because they engage both hearing and sight senses.